When Nursing Care and Clinical Trials Coincide: A Qualitative Study of the Views of Nordic Oncology and Hematology Nurses on Ethical Work Challenges. (December 2018) - Godskesen, Tove E.; Petri, Suzanne; Eriksson, Stefan; Halkoaho, Arja; Mangset, Margrete; Pirinen, Merja; Nielsen, Zandra Engelbak
This study investigated the kinds of ethical challenges experienced by nurses in oncology and hematology when nursing care and research overlap in clinical trials, and how the nurses handle such challenges. Individual interviews with 39 nurses from Sweden, Denmark, and Finland indicated that all nurses were positive about research, considering it essential for developing the best care. Ethical challenges exist, however; the most difficult were associated with the end-of-life patients, no longer responsive to standard therapy, who eagerly volunteer for cutting-edge drug trials in the hope of gaining therapeutic benefit. Many nurses lacked systematic strategies for addressing such challenges but found support from their nursing colleagues and relied on the research protocols to guide them.